2008
DOI: 10.1128/aac.00458-08
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic Effect of Rifampin on the Efficacy of High-Dose Levofloxacin in Staphylococcal Experimental Foreign-Body Infection

Abstract: Since levofloxacin at high doses was more active than levofloxacin at conventional doses and was the best therapy alone in a rat model of staphylococcal foreign-body infection, in this study we tested how these differences affect the activities of their respective combinations with rifampin in vitro and in vivo. In vitro studies were performed in the log and stationary phases. By using this model, rifampin at 25 mg/kg of body weight/12 h, levofloxacin at 100 mg/kg/day, levofloxacin at 100 mg/kg/day plus rifamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…Dose-dependent effects of the companion drug have been described for beta-lactams and fluoroquinolones (17,35) but were not observed with oxacillin in our experiment. Similar results were obtained with oxacillin at 2ϫ and 4ϫ MIC.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Dose-dependent effects of the companion drug have been described for beta-lactams and fluoroquinolones (17,35) but were not observed with oxacillin in our experiment. Similar results were obtained with oxacillin at 2ϫ and 4ϫ MIC.…”
Section: Discussionmentioning
confidence: 52%
“…However, its effect remains poorly defined, since the number of supporting human studies is limited and most of them have been underpowered (10,18,22,29). Moreover, recently performed in vitro studies have demonstrated antagonistic effects after addition of rifampin in experimental foreign body infection and endocarditis models (15,17).…”
mentioning
confidence: 99%
“…Of interest, during the first 24 h, rifampin antagonized and delayed the bactericidal activity of daptomycin against MRSA B346846, and gentamicin antagonized and delayed the bactericidal activity of daptomycin against both isolates. Although contradictory results can often be found in the literature (31), antagonistic activity is often observed when rifampin is added to bactericidal agents in high-inoculum infections and against biofilm-forming S. aureus (29,31,34). In addition, the inhibition of bacterial RNA synthesis may be responsible for delaying the killing activities of cell-wall-active agents.…”
Section: Discussionmentioning
confidence: 76%
“…In a retrospective cohort study of VRE bloodstream infections, treatment with daptomycin or linezolid demonstrated no difference in mortality; however, infection with E. faecium and concurrent treatment with rifampin or gentamicin were independent risk factors for mortality (54). Antagonistic activity is often observed when rifampin is added to bactericidal agents in high-inoculum infections, due to high rates of mutations conferring resistance (ϳ1 in 10 6 ) (31,55,56). The in vitro model demonstrated antagonism with rifampin.…”
Section: Discussionmentioning
confidence: 99%